2016
DOI: 10.1016/j.jgr.2015.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Increase in apoptotic effect of Panax ginseng by microwave processing in human prostate cancer cells: in vitro and in vivo studies

Abstract: BackgroundGinseng, which is widely used in functional foods and as an herbal medicine, has been reported to reduce the proliferation of prostate cancer cells by mechanisms that are not yet fully understood.MethodsThis study was designed to investigate the changes in ginsenoside content in ginseng after treatment with a microwave-irradiation thermal process and to verify the anticancer effects of the extracts. To confirm the anticancer effect of microwave-irradiated processed ginseng (MG), it was tested in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 29 publications
0
37
0
Order By: Relevance
“…Extracts from traditionally-cultivated Panax ginseng plants have been found to have anti-carcinogenic effects against various human cancer cell lines (stomach, cervical, colorectal, breast adenocarcinoma, lung carcinoma) (Lee et al , 2016 with IC 50 values ranging between 0.25 and 2.84 mg mL −1 depending on the tested cell line (Lee et al , 2016; similar values were obtained in the present study for our P. quinquefolium extracts. In contrast, Park et al (2016) reported P. ginseng root extract to have much stronger anticancer activity against prostate cancer cell lines (IC 50 0.05-0.075 mg mL −1 ).…”
Section: The Effects Of Fhr and Bhr On The Viability Of Glioblastomamentioning
confidence: 90%
“…Extracts from traditionally-cultivated Panax ginseng plants have been found to have anti-carcinogenic effects against various human cancer cell lines (stomach, cervical, colorectal, breast adenocarcinoma, lung carcinoma) (Lee et al , 2016 with IC 50 values ranging between 0.25 and 2.84 mg mL −1 depending on the tested cell line (Lee et al , 2016; similar values were obtained in the present study for our P. quinquefolium extracts. In contrast, Park et al (2016) reported P. ginseng root extract to have much stronger anticancer activity against prostate cancer cell lines (IC 50 0.05-0.075 mg mL −1 ).…”
Section: The Effects Of Fhr and Bhr On The Viability Of Glioblastomamentioning
confidence: 90%
“…Cancer stem cells (CSCs) have been regarded as the root of tumor progression and drug resistance, however, there is no effective drug targeting CSCs yet. Ginsenoside is an important active ingredient of ginseng and it has been used as an anticancer Chinese medicine in the treatment of malignant tumors such as melanoma and prostate cancer . Ginsenoside Rg3, the main component of Ginsenoside, has been shown to inhibit tumor progression and chemoresistance, for example, Ginsenoside Rg3 attenuates temozolomide resistance and epithelial‐mesenchymal transition (EMT) progression in glioblastoma; Ginsenoside Rg3 inhibits prostate cancer cell proliferation through inducing cell cycle arrest .…”
Section: Introductionmentioning
confidence: 99%
“…Ginsenoside 20(R)-Rg3, but not 20(S)-Rg3, suppressed lung cancer migration, invasion, and anoikis resistance [18]. However, ginsenoside 20(S)-Rg3, but not 20(R)-Rg3, induced apoptotic cell death in human gastric cancer AGS cells by activating caspases [19], [20].…”
Section: Resultsmentioning
confidence: 95%